Комплексы с большими двупластинчатыми фибулами из Лучистого - Айбабин, А.И. (Материалы по археологии, истории и этнографии Таврии, 1995)
Большие двухпластинчатые фибулы из Юго-Западного Крыма обычно датировали по комплексам вещей из Суук-Су, которые Н. И. Репников отнес к V-VII вв.. В. К. Пудовин аргументированно предложил омоложение названных комплексов до середины VI в.. По мнению А. К. Амброза, рассматриваемые южнокрымские фибулы изготовлялись на полуострове с середины VI в. по образцам из Подунавья. Новые комплексы, найденные мною в 1982 и 1984 гг. в многослойном склепе 10 и в склепе 42 в Лучистом у подножия г. Демерджи близ г. Алушты, позволяют более доказательно обосновать разработанную А. К. Амброзом хронологию и типологию однотипных фибул . В настоящей статье впервые публикуется весь инвентарь этих склепов Large bi-plated brooches from the South-Western Crimea were usually dated by the complexes of things from Suuk-Su, N. I. Repnikov dated them back to the 5th - 7th cent.. V. K. Pudovin put forward an idea that the above mentioned complexes were younger up to the mid-6th cent.. A. K. Ambroz thought that South-Crimean brooches under consideration were manufactured on the peninsula from the mid- 6th cent, using the models from the Danubian Region. In 1982 and 1984 I found new complexes in manylayered vault 10 and in vault 42 in Luchistoe at the slope of Demerdji-mountain near the town of Alushta which allow us to substantiate the chronology and typology of the same type brooches worked out by A. K. Ambroz in a more argumented way. The whole inventory of these vaults is published in this article for the first time.